POLA KOMUNITAS GUA DI SAMPUNG, PONOROGO - Nurani, Indah Asikin (BRIN, 2003)
Each cave / rockshelters shows that the use of the cave land between Lawa Cave and Layah, Ngalen, and Sulur rockshelters shows a striking difference. It seems that the Lawa Cave in this community is used as the main cave, where all community activities take place. Meanwhile, the Layah, the Ngalen, and the Sulur rockshelters are used for supporting activities. This is based on a comparison of the excavation results between the Lawa Cave and the surrounding rockshelters. The findings of artifacts, ecofacts and features in the Lawa Cave varied more in quality and quantity compared to the surrounding recesses whose findings tended to be homogeneous in the form of lithic artifacts. In addition, based on the findings of artifacts in the Layah rockshelter, it shows that there is a development in their use. Initially (the lower layer) Layah was used as a stone tool workshop, then later (the upper layer) was dominated by the discovery of pottery. Meanwhile, the ecofac findings around the Lawa Cave tend to be minimal. It can be concluded that the pattern of the cave community in Sampung consists of a main cave with an ongoing cultural complexity and a supporting cave / rockshelter that is used for secondary activities.